Oxidized lead mineral flotation - Azañero Ortiz, Angel (2002)
The main oxidized lead minerals are: cerussite and anglesite, which due to their crystallography and wettability should not be buoyant, for this reason it is necessary to study the flotation properties for these minerals, the main ones are: solubility, surface physico-chemical , thermodynamics, fines content and others, it is concluded that anglesite is less buoyant than cerussite, both can be floated directly with amyl xanthate: long-chain hydrocarbon collector and cationic collectors such as alamine 26-D. The flotation of oxides improves when they are previously sulfurized before adding xanthate type collector, obtaining economically acceptable results. The above is applied to a polymetallic mineral of galena, sphalerite and cerussite; up to four flow charts are discussed, two are experimented, and with the bulk flotation scheme Pb-Zn, followed by flotation of oxides, after sulfurization with sodium sulfide excellent results are obtained, taking into account the complexity of the mineral.